2008
DOI: 10.1007/s10633-007-9103-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes of electroretinogram without improvement of retinal circulation after radial optic neurotomy for central retinal vein occlusion

Abstract: Significant improvements were observed in the b/a wave ratio of the standard combined ERGs after surgery in eyes with CRVO. The improvement of retinal function was most likely due to improved oxygenation of retina caused by vitrectomy and not by RON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…During postoperative observation, vitreous hemorrhage occurred in one case (7.1%), which was completely absorbed within 3 weeks, and subretinal hemorrhage occurred in three cases (21.4%), which were subsequently absorbed (21). Sato et al (28) performed RON on 10 eyes of 10 CRVO patients (including two ischemic and eight nonischemic) after vitrectomy. Compared with the average bestcorrected visual acuity and average fovea thickness before and 3 months after operation, the average amplitudes of A wave and B wave did not change significantly through the analysis of standardized combined electroretinograms (ERGs).Still the B/ A wave ratio increased significantly and the B wave incubation period shortened significantly in six eyes.…”
Section: The Occurrence and Development Of Various Adverse Eventsmentioning
confidence: 99%
“…During postoperative observation, vitreous hemorrhage occurred in one case (7.1%), which was completely absorbed within 3 weeks, and subretinal hemorrhage occurred in three cases (21.4%), which were subsequently absorbed (21). Sato et al (28) performed RON on 10 eyes of 10 CRVO patients (including two ischemic and eight nonischemic) after vitrectomy. Compared with the average bestcorrected visual acuity and average fovea thickness before and 3 months after operation, the average amplitudes of A wave and B wave did not change significantly through the analysis of standardized combined electroretinograms (ERGs).Still the B/ A wave ratio increased significantly and the B wave incubation period shortened significantly in six eyes.…”
Section: The Occurrence and Development Of Various Adverse Eventsmentioning
confidence: 99%
“…On the other hand, some studies revealed that RON induce the development of retinochoroidal shunt vessels in 46.7-83.3% of patients and this may represent the mechanism of any beneficial effect this surgical procedure [67][68][69][70][71] . In addition, several authors suggested that the creation of RON involves a PPV and the beneficial effects of RON are due to this alone [72,73] . Nomoto et al [68] treated 15 eyes with CRVO by performing RON to evaluate the effects of RON on retinal circulation in patients with CRVO by indocyanine green (ICG) videoangiography and a computer-assisted image analysis.…”
mentioning
confidence: 99%